KONTRIBUSI MOTIVASI BERPRESTASI DAN SOFT SKILL TERHADAP HASIL BELAJAR MATEMATIKA PADA MAHASISWA JURUSAN S1 PENDIDIKAN MATEMATIKA IKIP PGRI BALI - Juwana, IDP; Wiguna, DGE Sastra (Widyadari: Jurnal Pendidikan, 2019)
This study aims to determine: (1) contribution the achievement motivation to mathematic result study of undergraduate students education of mathematic Departement, (2) contribution the soft skill to mathematic result study of undergraduate students education of mathematic Departement, and (3) contribution the achievement motivation and soft skill to mathematic result study of undergraduate students education of mathematic Departement.This study is a correlational study. The research was conducted at undergraduate degree education of mathematic Departement IKIP PGRI BALI. The sample in this study as many as 75 people, sampling is done using strata random sampling technique. Methods of data collection in the form of tests and questionnaires using a Likert scale. Methods of data analysis used was multiple regression.The results showed that (1) the achievement motivation contributes to mathematic result study of undergraduate students education of mathematic Departement (r = 0.60, p <0.05 and t = 6,41, p <0.05). (2) the soft skill contributes to mathematic result study of undergraduate students education of mathematic Departement (r = 0.8, p <0.05 and t = 11,58, p <0.05)). (3) the achievement motivation and soft skill contributes to mathematic result study of undergraduate students education of mathematic Departement (r = 0.84, p <0.05 and F = 83,31, p <0.05) as well as having effective contribution by 70% .